SYRIAN REFUGEES IN TURKEY: Implementation of Turkey Open Door Policy in Dealing with Syrian Refugees - Muhammad Fawwaz Syafiq Rizqullah; Fadhillah Jofianta Putri; Shania Afridita; Halim Purnomo (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2020)
The Syria refugees’ problems in the Middle East with most of the victims are Muslim is the humanitarian cases which still cannot be fixed until nowadays. In order to response that problems Turkey government which has majority society are Muslim and supported by the geographical location because Turkey has located nearby Syria take action and created policy to support Syria refugees in order to help their life. However, the aim of this paper is to puzzle out the Turkey aim in implementing the open-door policy by Turkey government under president Recep Tayyip Erdogan. By using Regime theory by qualitative research method based on journal, book, and other credible resource. This paper find out several if there is some reason behind why Turkey implementing the policy toward Syria refugees there are first, become the reason to enter as the full members of EU, second, in order to gain bargaining position and lifting the name of Turkey as the country who care about humanitarian cases in international scale, and third as the evidence of Turkey if Turkey has ratifying the UN convention on human right. This paper also explains about how Turkey action in facilitating the Syria refugees and try to protect their right and life. And lastly, this paper also gives information about challenging that Turkey dealing in implementing this policy to help the Syria refugees.